2021
DOI: 10.1016/j.cmi.2020.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 IgG antibodies in a large prospective cohort study of elite football players in Germany (May–June 2020): implications for a testing protocol in asymptomatic individuals and estimation of the rate of undetected cases

Abstract: Objectives Elite professional football players and staff are a unique group that might give insight into the epidemiology of SARS-CoV-2 infections in Germany and thus can serve as a model for a geographical distribution and an estimation of undetected infections. Methods In this prospective cohort study seroprevalence was determined twice in May and June 2020 in players and staff from German Bundesliga. As screening assays a commercial ELISA (Euroimmun) and a CLIA (Roch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The prevalence of COVID-19 was higher among these athletes than it was in the Croatian population during the study period (<9%) [ 29 ]. Additionally, according to previously published studies on professional athletes and on soccer players in particular, indicated a lower burden of COVID-19 (less than 5%) [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The prevalence of COVID-19 was higher among these athletes than it was in the Croatian population during the study period (<9%) [ 29 ]. Additionally, according to previously published studies on professional athletes and on soccer players in particular, indicated a lower burden of COVID-19 (less than 5%) [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 91%
“…A prospective cohort study on the players and staff from the German Bundesliga in 2020 showed similar seroprevalence from 1184 players and staff in May (1.99%) and June (2.09%) [ 30 ]. In a study on two teams from Denmark’s top two soccer leagues, the players were tested weekly for 11 consecutive weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the repercussions of the COVID-19 pandemic on the epidemiological and sporting profiles, life and health habits, and clinical characteristics of Brazilian athletes. Although the high number of COVID-19 cases among athletes itself indicates the requirement of a better understanding of the prevalence, associated factors, and behaviour of SARS-CoV-2 infection [ 14 , 24 ], few studies have focused on this subject [ 25 27 ], and highly variable results have been reported. For example, the prevalence of COVID-19 was observed to be 2% in a prospective study of 812 professional soccer players and 372 staff members from the German Bundesliga [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, overall study estimates were largely below 10%, however higher seroprevalence was noted in a number of population-specific, regional or local studies (29,36,43,(50)(51)(52)(53)(54), with suggestion of earlier undetected transmission in some countries (24,26,34,55). A total of 16 studies reported seroprevalence estimates spanning multiple timepoints or stages of the epidemic (14, 15,27,31,32,47,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. In a serial cross-sectional study in France (61), residual blood sampled before, during and after a national lockdown showed a seroprevalence of 0.41%, 4.14%, and 4.93%, respectively.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%